2018
DOI: 10.3390/ma11030337
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Compensated InGaAsP Superlattices for Defect Reduction of InP Grown on Exact-Oriented (001) Patterned Si Substrates by Metal Organic Chemical Vapor Deposition

Abstract: We report on the use of InGaAsP strain-compensated superlattices (SC-SLs) as a technique to reduce the defect density of Indium Phosphide (InP) grown on silicon (InP-on-Si) by Metal Organic Chemical Vapor Deposition (MOCVD). Initially, a 2 μm thick gallium arsenide (GaAs) layer was grown with very high uniformity on exact oriented (001) 300 mm Si wafers; which had been patterned in 90 nm V-grooved trenches separated by silicon dioxide (SiO2) stripes and oriented along the [110] direction. Undercut at the Si/Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In Figure 15d, it was shown that the employment of three sets of In 0.18 Ga 0.82 As/GaAs SLSs DFLs effectively blocked and annihilated the TDs. In the InP/Si platform, the DFLs based on InGaAs/InP, In(Ga)AsP/InP, (In)GaP/InP, and so on [149,170,[225][226][227][228][229][230] have been also commonly adopted. For instance, Shi et al [149] reported the effect of In0.73Ga0.27As/InP SLSs DFLs on the reduction of TDD in InP grown on on-axis (001) Si.…”
Section: Strained-layer Superlattices Defect Filter Layermentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 15d, it was shown that the employment of three sets of In 0.18 Ga 0.82 As/GaAs SLSs DFLs effectively blocked and annihilated the TDs. In the InP/Si platform, the DFLs based on InGaAs/InP, In(Ga)AsP/InP, (In)GaP/InP, and so on [149,170,[225][226][227][228][229][230] have been also commonly adopted. For instance, Shi et al [149] reported the effect of In0.73Ga0.27As/InP SLSs DFLs on the reduction of TDD in InP grown on on-axis (001) Si.…”
Section: Strained-layer Superlattices Defect Filter Layermentioning
confidence: 99%
“…For example, the TDD of InP-based materials remains on the order of 10 8 cm −2 , while, in GaAs-based materials, the order of 10 6 cm −2 can be achieved. The reason for the discrepancy is not clearly understood, but it is believed to be due to the phase separation in the SLSs and/or the high density of dislocations arising from larger lattice mismatch in InP/Si than In the InP/Si platform, the DFLs based on InGaAs/InP, In(Ga)AsP/InP, (In)GaP/InP, and so on [149,170,[225][226][227][228][229][230] have been also commonly adopted. For instance, Shi et al [149] reported the effect of In 0.73 Ga 0.27 As/InP SLSs DFLs on the reduction of TDD in InP grown on on-axis (001) Si.…”
Section: Strained-layer Superlattices Defect Filter Layermentioning
confidence: 99%
“…The TDs, which can act as non-recombination centers and electrical channels, can seriously deteriorate the material quality and device performances [7,8]. Various epitaxial methods have been investigated for the suppression of TDs during the growth of materials with large lattice mismatch, which include graded buffer layers [9], dislocation filtering layers [10], interlayer structures [11] and strain compensation [12]. However, little has been reported on the integration of GaInAsSb based devices on GaAs substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing technologies, flip-chip bonding and micro-transfer printing are easier to implement, but the two approaches are also confronted by the chip and transfer-layer size, interconnect size and losses, and the complexity of manufacture. Therefore, direct epitaxial growth is considered as the most promising approach in the future [12,13]. However, it still faces enormous challenges owing to the large lattice mismatch, thermal mismatch, and antiphase boundaries caused by crystal polarity difference.…”
Section: Introductionmentioning
confidence: 99%